American Society of Clinical Oncology 2012 annual meeting: new optimism for fighting platinum-resistant ovarian cancer. (September 2012) - Markman, Maurie
Maurie Markman speaks to Alice O'Hare, Commissioning Editor, about the 2012 annual meeting of the American Society of Clinical Oncology (ASCO) held in Chicago (IL, USA) on 1–5 June 2012. Maurie Markman is Senior Vice President for Clinical Affairs and National Director for Medical Oncology, for the Cancer Treatment Centers of America. For more than 25 years Markman has been engaged in clinical research in the area of gynecologic malignancies, with a particular focus on new drug development and exploring novel management strategies in female pelvic cancers. Prior to assuming his current position, Markman served as Vice President for Clinical Research at the University of Texas MD Anderson Cancer Center (TX, USA). Additional previous positions include Director of the Cleveland Clinic Cancer Center, as well as Chairman at the Department of Hematology/Medical Oncology at the Cleveland Clinic (OH, USA), and Vice-Chairman at the Department of Medicine, Memorial Sloan-Kettering Cancer Center (NY, USA). Markman has been the primary author or co-author on more than 1000 published peer-reviewed manuscripts, reviews, book chapters, editorials or abstracts, and he has written, edited or co-edited 16 books on various topics in the management of malignant disease, including Atlas of Cancer and the most recent edition of Principles and Practice of Gynecologic Oncology . In addition, Markman has served on numerous editorial boards, including Clinical Investigation, the Journal of Clinical Oncology and Gynecologic Oncology ; and he is currently Editor-in-Chief of Oncology and Case Reports in Oncology (Karger Press).